Positron interactions with water–total elastic, total inelastic, and elastic differential cross section measurements - Tattersall, Wade J.; Chiari, Luca; Machacek, J.R.; Anderson, Emma; White, Ron D.; Brunger, M.J.; Buckman, Stephen J.; Garcia, Gustavo; Blanco, Francisco; Sullivan, James P. (American Institute of Physics, 2014)
Utilising a high-resolution, trap-based positron beam, we have measured both elastic and inelastic scattering of positrons from water vapour. The measurements comprise differential elastic, total elastic, and total inelastic (not including positronium formation) absolute cross sections. The energy range investigated is from 1 eV to 60 eV. Comparison with theory is made with both R-Matrix and distorted wave calculations, and with our own application of the Independent Atom Model for positron interactions.